Single-event upset simulation and detection in configuration memory - Austin, Hezekiah; Major, Chris; Barney, Colter; Williams, Justin; Becker, Zachary; Smith, Mackenzie; LaMeres, Brock (Frontiers in Space Technologies, 2025)
Single-event upsets (SEUs) from radiation strikes in configuration memory are potentially catastrophic due to their widespread effects. For field-programmable gate arrays (FPGAs), faults in configuration memory propagate into the implemented logic design at the hardware interconnection level, leading to unpredictable results. Two payloads consisting of a pair of quad modular redundant (QMR) FPGA-based processor were deployed to the International Space Station (ISS) for 13 months. During operation, these payloads experienced a number of faults from radiation, including one payload that experienced a rare multi-core fault. Investigation suggested that the multi-core fault was the result of a single-event effect (SEE), either directly in a voter on the logic design or as an SEE in the FPGA configuration memory changing the implemented logic. An injection procedure for the FPGA’s configuration memory was developed to simulate radiation strikes and test fault detection. The injection procedure was paired with the QMR processor. This provided a full configuration memory testing environment, where the implemented logic design was capable of detecting faults propagating from the FPGA’s configuration memory. Injection throughout the configuration memory was used to create a map of particularly vulnerable locations in configuration memory and the implemented logic design. Testing with injected faults produced similar results to the multi-core fault observed in orbit on the payload. The testing procedure provides a comprehensive testing strategy, which pairs systematic injection in configuration memory with a logic design capable of detecting the induced errors to localize the propagating fault in the design.